THEORETICAL AND LEGAL ANALYSIS OF APPROACHES TO THE DEFINITION AND CHARACTERISTICS OF COUP D’ETAT AS TECHNOLOGY TO DESTABILIZE SOCIAL AND POLITICAL SYSTEM IN THE CONTEXT OF STRATEGY OF RESPONSE DEVELOPMENT - Onyshchenko O.A. (Pressing Problems of Public Administration, 2016)
The article deals with the analysis of theoretical and methodological approaches to the de nitions and characteristics of state coups as a type of destabilization technologies of the socio-political system of the state in the context of national security. The necessity of a systematic approach to the de nition of prerequisites and prediction of consequences of the destabilization policies of social and political systems in order to develop public response methods.